Effects of seat parameters and sitters' anthropometric dimensions on seat profile and optimal compressed seat pan surface. (November 2018) - Wang, Xuguang; Cardoso, Michelle; Beurier, Georges
Abstract: Designing one seat for multi-sitters and multi-activities is challenging especially in a very restrained aircraft economy class cabin. In this paper, the effects of seat parameters and sitters' anthropometric dimensions on seat profile and optimal compressed seat pan surface were studied using a newly built multi-adjustable experimental seat. The 'optimal' seat pan contact surface was obtained by controlling the height of 52 cylinders so that the normal contact force was distributed to all cylinders as evenly as possible. With 13 other motorized adjustments controllable by a computer, individual seat profile in the symmetry plane such as seat height, seat pan length, seat pan angle, lumbar protrusion and headrest position were also studied. Data were collected from 36 men and women of varying body size testing 40 seat configurations. Parametric models were obtained for predicting seat profile and optimal compressed seat pan seat surface in function of seat pan and back rest angles for two sitting postures. It is expected that the proposed parametric models provide necessary reference values in seat development for a better fit of a target population of sitters with large varying body size. Highlights: Multivariable regression equations were obtained to predict body size dependent preferred seat profile parameters. Optimal compressed seat pan surface was by obtained by evenly distributing contact force from an initially flat surface. PCA based regression equations were obtained to predict optimal compressed seat pan surface. Range of variations of seat parameters are provided for six target sitters with varying height and BMI.